2010
DOI: 10.1007/s00251-010-0427-2
|View full text |Cite|
|
Sign up to set email alerts
|

Polymorphic SVA retrotransposons at four loci and their association with classical HLA class I alleles in Japanese, Caucasians and African Americans

Abstract: Polymorphic insertion frequencies of the retrotransposons known as the "SVA" elements were investigated at four loci in the MHC class I genomic region to determine their allele and haplotype frequencies and associations with the HLA-A, -B or -C genes for 100 Japanese, 100 African Americans, 174 Australian Caucasians and 66 reference cell lines obtained from different ethnic groups. The SVA insertions representing different subfamily members varied in frequency between none for SVA-HF in Japanese and 65% for SV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 42 publications
2
27
0
Order By: Relevance
“…UTR were listed for informative purposes as the network is based on protein sequences. The resulting network revealed an HLA-A clustering in accordance with other studies [45], [46], [47]. The five HLA-A lineages previously defined by Gu et al [45] are also indicated.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…UTR were listed for informative purposes as the network is based on protein sequences. The resulting network revealed an HLA-A clustering in accordance with other studies [45], [46], [47]. The five HLA-A lineages previously defined by Gu et al [45] are also indicated.…”
Section: Resultssupporting
confidence: 88%
“…In order to establish the relationships among the HLA-A and HLA-G haplotypes, a Median Joining (MJ) network [44] based on protein sequences was constructed using the program Network (www.fluxus-engineering.com/network). The HLA-A alleles were grouped into five lineages previously defined [45], [46], [47].…”
Section: Methodsmentioning
confidence: 99%
“…The frequency of this presence or absence of specific SVAs located in HLA genes has shown to be variable between groups with different ethnic origins [53]. This demonstrates the variability of SVA insertions between individuals; our study extends the analysis of their polymorphic nature to include the variation found in the CCCTCT hexamer repeat and provides further evidence of the already characterised variation in the second domain of the central VNTR (Table 2).…”
Section: Discussionsupporting
confidence: 68%
“…These class II and OR‐POALINs would be an useful addition to the class I POALINs for future population studies because the more the Alu loci are used in a comparison of populations, the better the average consensus plot will be for discerning the interrelation of different populations and providing a clearer picture of POALIN and HLA relationships between populations. Apart from the polymorphic Alu insertions within the HLA genomic region, there are other dimorphic retrotransposons such as SVA, L1 (Kulski, Shigenari, & Inoko, ), LTR (Kulski et al, ) and HERVs (Kulski et al, ) that also could be used in population MHC genetic diversity studies. Furthermore, sequencing these MHC class I and II Alu insertions by the Sanger method or next‐generation sequencing to detect SNPs within their aligned sequences could provide an additional useful layer of analysis within and between populations as was previously shown for the solitary LTR indel MER9 in the HLA class I alpha block (Kulski et al, ).…”
Section: Resultsmentioning
confidence: 99%